The trial of Emma Cunningham : murder and scandal in the Victorian era - Jenkins, Brian (Brian A.) (Jefferson, North Carolina : McFarland & Company, Inc., Publishers, 2020)
"The alleged 1857 murder of a wealthy Bond Street dentist by a Emma Cunningham, a young widow he was believed to be sexually involved with, served to distract many New Yorkers from the deepening national crisis over slavery in the United States. Public anxieties seemed well founded-domestic murders committed by women were believed to be increasing sharply, jeopardizing society's patriarchal structure. The penny press created public demand for a swift solution. The inadequacy of the city police, complicated by the state's decision to install a new force, resulted in the rival forces battling it out on the streets. Elected coroners conducting inquests and elected D.A.'s prosecuting alleged culprits fed a tendency to rush to judgment. New York juries, all men, were reluctant to send a middle class woman to the gallows. At trial, Cunningham proved a formidable and imaginative member of the so-called weaker sex and was acquitted. This reexamination places the story in its social and political context."--
Murder in Bond Street -- The inquest opens -- The coroner's theory -- Clinton intervenes -- Verdicts and indictments -- In the court of public opinion -- The case for the people -- The defense -- The response to the verdict -- The bogus baby melodrama -- The question of guilt.
Description based on print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Cunningham, Emma Augusta -- Trials, litigation, etc; Burdell, Harvey, -- -1857 -- Estate; Burdell, Harvey, -- 1811-1857; Cunningham, Emma Augusta; Trials (Murder) -- New York (State) -- New York; Procès (Meurtre) -- New York (État) -- New York; Decedents' estates; Trials (Murder); New York (State) -- New York; Trial and arbitral proceedings; Trials, litigation, etc; Trial and arbitral proceedings; Comptes rendus de procès et d'arbitrage.